INFLUENCE OF ATTACHMENT STYLES ON ESTABLISHMENT OF ADOLESCENTS’ IDENTITY AMONG SECONDARY SCHOOL STUDENTS FROM BLENDED FAMILIES IN KIAMBU COUNTY - Lucy Gachenia; Ruth Kamunyu; Nathan Chiroma (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Parents adopt different attachment styles in parenting their children. This phenomenon is more profound in blended families where there are many relationships that can lead to many problems. However, with appropriate attachment styles adopted by step parents such challenges can be mitigated. The purpose of this study was to examine influence of attachment styles on establishment of adolescents’ identity among secondary school students from blended family in Kiambu County, Kenya. Attachment theory by Bowlby guided this study. The study adopted a mixed method approach, descriptive causal effect design and pragmatic paradigm to guide the study. Multi-stage sampling method and inclusive /exclusive criteria were used. To begin with, the study adopted survey method as the sampling technique because the total population of adolescents that came from blended families was unknown. Simple random sampling was used to select 9 schools and also determine the 5 classes to be sampled in each of these schools. The 5 classes had a population of 55 students each. A short questionnaire with demographic data of students was issued to all the students (2475) in a bid to elicit the adolescents from the said classes that came from blended families in the 9 schools. A total number of 208 adolescents from blended families in the 9 schools was elicited and this was considered a sufficient sample size. In addition, simple random sampling was used to sample 24 respondents to form 4 focus groups while purposive sampling was used to sample 4 counsellors from 9 schools for in-depth interview. Data was collected using questionnaires, counsellors’ interview schedule and focus group discussions. Inventory for Parent and Peer Attachment Scale and Identity Style Inventory were used as measuring tools. Data was analysed through descriptive statistics, statistical assumption tests, correlation tests- T- test, and MANCOVA analysis while qualitative data was analysed by use of narrative analysis. Findings were presented in form of tables while interview data was presented in narrative form. Permission to conduct the study was obtained from the National Council for Science and Technology, the Kiambu County Government, Ethical approval was sought from accredited IERC (Institutional Ethics Review Committee) as well as a written informed consent from the school administration. Results indicated that attachment styles adopted by step parents influence the establishment of adolescent informational, commitment and diffuse avoidant identity styles but not normative identity style. The study will benefit Ministry of Education, counsellors, parents, families and society.